2018
DOI: 10.1371/journal.pone.0199139
|View full text |Cite
|
Sign up to set email alerts
|

Egocentric networks and physical activity outcomes in Latinas

Abstract: ObjectiveDespite data linking the social environment to physical inactivity in Latinas, research on social network predictors of physical activity (PA) is limited. This study examined social network predictors of PA change in Latinas.MethodsEgocentric network data were collected from 102 adult Latinas (egos) participating in a randomized controlled PA intervention trial for underactive women. Moderate-to-vigorous PA (MVPA) was measured in minutes per week using the 7-Day PA Recall Interview and accelerometers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
(68 reference statements)
0
13
0
Order By: Relevance
“…These findings are confirmed by previous studies. 16,31,35 Studies have indicated that the company of peers increases physical activity, 36 as well as sedentary behavior. 37 In consequence, friends' behavior represents an important resource for physical activity and sedentary behavior.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are confirmed by previous studies. 16,31,35 Studies have indicated that the company of peers increases physical activity, 36 as well as sedentary behavior. 37 In consequence, friends' behavior represents an important resource for physical activity and sedentary behavior.…”
Section: Discussionmentioning
confidence: 99%
“…48 More recent evidence from Marquez et al (2018) showed larger networks were associated with increased moderate to vigorous exercise. 49 While mechanisms that explain this association are still under-theorized, some evidence suggests that larger networks provide greater social support by increasing opportunities and tangible/ instrumental support that promote physical activity. [49][50][51] Larger network sizes have also been shown to facilitate mirroring or aspirations related to body size and exercise.…”
Section: Discussionmentioning
confidence: 99%
“…49 While mechanisms that explain this association are still under-theorized, some evidence suggests that larger networks provide greater social support by increasing opportunities and tangible/ instrumental support that promote physical activity. [49][50][51] Larger network sizes have also been shown to facilitate mirroring or aspirations related to body size and exercise. 51 Larger networks provide emotional support that is associated with health screening and diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, you will need to specify how many people your participants will be allowed to list as their network. For a first orientation, you may want to consult previous studies that have employed egocentered networks (e.g., Armstrong & Kammrath, 2015;Aschbrenner et al, 2018;Asendorpf & Wilpers, 1998;Borschel et al, 2019;Greischel, Noack, & Neyer, 2016Marquez et al, 2018;Wyngaerden et al, 2019;Zimmermann & Neyer, 2013) for typical as well as maximum network sizes. Another way to approach this is to pilot your method of assessing your network of interest (including your name generators) in a small sample of face-to-face interviews.…”
Section: Considerations In Advancementioning
confidence: 99%